The Wiley-Blackwell handbook of operant and classical conditioning - McSweeney, Frances K.; Murphy, Eric S. (Chichester, Sussex, UK : Malden, MA : Wiley-Blackwell, 2014)
'This combined survey of operant and classical conditioning provides professional and academic readers with an up-to-date, inclusive account of a core field of psychology research, with in-depth coverage of the basic theory, its applications, and current topics including behavioral economics. Provides comprehensive coverage of operant and classical conditioning, relevant fundamental theory, and applications including the latest techniques Features chapters by leading researchers, professionals, and academicians Reviews a range of core literature on conditioning Covers cutting-edge topics such as behavioral economics'--
'This handbook on operant and classical conditioning reflects the acknowledged similarities in the fundamental principles of the two varieties of learning behavior'--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Operant conditioning; Classical conditioning; Electronic books; Electronic books